ANALISIS ELECTRONIC WORD OF MOUTH (E-WOM), PROMOSI MEDIA SOSIAL DAN RESTO ATMOSPHERE DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN DI GOODMOOD COFFEE PONOROGO - Farida Ayu Anggraini; Destriyanto Pristi Ayuningtyas, Eka; Adjie, Setyo (JURNAL ILMIAH EDUNOMIKA, 2025)
This research investigates how Electronic Word of Mouth (E-WOM), social media promotions, and the restaurant atmosphere influence consumers’ purchasing decisions at Goodmood Coffee Ponorogo. Purchasing behavior is not impulsive but shaped through a process influenced by prior experiences, preferences, and exposure to relevant information. A quantitative method was applied using a survey technique, and data were gathered via a Likert-scale questionnaire. The study involved 95 selected respondents, chosen based on specific criteria to serve as the sample, data were analyzed using SPSS 25. Findings indicate that E-WOM, social media promotion, and the ambience of the café have both individual and combined effects on consumers’ purchasing decisions. Among these, E-WOM plays a dominant role by shaping consumer preferences through shared positive reviews. Meanwhile, engaging promotional content on social media contributes to favorable consumer perception. Additionally, a pleasant and inviting café atmosphere enhances the customer experience, supporting their decision to purchase.